1995
DOI: 10.1111/j.1476-5381.1995.tb15872.x
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus and E. coli LPS‐induced NO‐dependent hyporesponsiveness to noradrenaline in isolated intrapulmonary arteries of neonatal piglets

Abstract: The effects of endotoxin (E. coli lipopolysaccharide, LPS) and heat inactivated group B Streptococcus (GBS) were studied on the contractile responses to noradrenaline (NA) in isolated pulmonary arteries and on the activity of the constitutive and inducible nitric oxide synthase (NOS) in lung fragments of neonatal piglets. Short‐term (≤ 5 h) incubation with LPS (1 μg ml−1) or GBS (3 × 107 colonies forming units ml−1) did not modify the vascular responsiveness to NA (10−8 M‐10−4 m) in isolated intrapulmonary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 34 publications
(39 reference statements)
3
18
1
Order By: Relevance
“…Moreover, aminoguanidine also reduces the circulatory failure and liver dysfunction caused by endotoxin in the rat , which is secondary to an enhanced formation of NO by iNOS heat-inactivated group B streptococci also resulted in induction of iNOS activity and vascular hyporeactivity to the contractile responses elicited by noradrenaline. This vascular hyporeactivity is prevented by pretreatment of the vessels with dexamethasone or the protein synthesis inhibitor cycloheximide, attenuated by the NOS inhibitor NG-nitro-L-arginine methyl ester (L-NAME), and augmented by the addition of L-arginine to the medium (Villamor et al, 1995). Thus, whole Gram-positive bacteria (Villamor et al, 1995) This study also demonstrates that dexamethasone and aminoguanidine attenuate the fall in Pao2, hence, respiratory dysfunction, caused by co-administration of LTA + PepG suggesting that NO mediates this adverse effect.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, aminoguanidine also reduces the circulatory failure and liver dysfunction caused by endotoxin in the rat , which is secondary to an enhanced formation of NO by iNOS heat-inactivated group B streptococci also resulted in induction of iNOS activity and vascular hyporeactivity to the contractile responses elicited by noradrenaline. This vascular hyporeactivity is prevented by pretreatment of the vessels with dexamethasone or the protein synthesis inhibitor cycloheximide, attenuated by the NOS inhibitor NG-nitro-L-arginine methyl ester (L-NAME), and augmented by the addition of L-arginine to the medium (Villamor et al, 1995). Thus, whole Gram-positive bacteria (Villamor et al, 1995) This study also demonstrates that dexamethasone and aminoguanidine attenuate the fall in Pao2, hence, respiratory dysfunction, caused by co-administration of LTA + PepG suggesting that NO mediates this adverse effect.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…This vascular hyporeactivity is prevented by pretreatment of the vessels with dexamethasone or the protein synthesis inhibitor cycloheximide, attenuated by the NOS inhibitor NG-nitro-L-arginine methyl ester (L-NAME), and augmented by the addition of L-arginine to the medium (Villamor et al, 1995). Thus, whole Gram-positive bacteria (Villamor et al, 1995) This study also demonstrates that dexamethasone and aminoguanidine attenuate the fall in Pao2, hence, respiratory dysfunction, caused by co-administration of LTA + PepG suggesting that NO mediates this adverse effect. The respiratory dysfunction in septic shock is charaterized by a reduction in pulmonary oxygen uptake resulting in a fall in Pao2 (Deitsch, 1992).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…The existing evidence is controversial, with reports suggesting that HPV is either increased (11,12) or unchanged (13,14) after acute inhibition of NO formation with L-arginine analogs during sepsis. After an endotoxin challenge, suppression of NOS2 expression with dexamethasone and inhibition of NOS2 activity by administration of L-arginine analogs restore vascular reactivity to vasoconstrictors in both systemic (15) and pulmonary vessels (16). However, the use of L-arginine analogs or dexamethasone to evaluate the role of NOS2 in the endotoxin-induced impairment of HPV is limited by the incomplete specificity of these agents for NOS2.…”
Section: Introductionmentioning
confidence: 99%
“…This effect may not be significant inasmuch as administration of superoxide dismutase did not attenuate GBS-induced pulmonary hypertension in the lamb (23). Additionally, during sepsis, there may be increased release of nitric oxide systemically (24,25), which can result in increased peroxynitrite levels. Peroxynitrite has been shown to inhibit endothelial nitric oxide synthase (eNOS) activity, although the mechanism is unknown (21).…”
Section: Navarrete Et Almentioning
confidence: 99%
“…The participation of these cytokines in the systemic inflammatory response syndrome and cardiovascular failure has been established and is described to contribute to the observed systemic hypotension (9,15). Second, sepsis induces nitric oxide synthase (iNOS) in the endothelial and vascular smooth muscle cells, enhancing vasodilatation especially during the late phase of sepsis (24,25). Moreover, Markewitz et al (27) demonstrated that ET-1 decreased iNOS mRNA in cytokine-stimulated rat epithelial cells and this effect was reversed by phosphoramidon.…”
Section: Navarrete Et Almentioning
confidence: 99%